Ocena temperamentu chorych z centralną surowiczą retinopatią. Doniesienie wstępne - Lesiewska-Junk, Hanna; Malukiewicz, Grażyna; Jaracz, Marcin; Brożek-Pestka, Marzenna; Borkowska, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To assess differences in temperament in patients with central serous retinopathy and healthy subjects. Material and methods: 20 patients diagnosed with acute central serous retinopathy was put to the questionnaire: Cloninger’s Temperament and Character Inventory. Results: Lower scores in novelty seeking (NS) (t = -2.43; p<0.05) scale and its NS2 (t = -2.12; p<0.05), and NS3 (t = -2.66; p<0.05) subscales, as well as higher scores in harm avoidance HA4 subscale in CSR patients ,were found. Conclusions: There is a different profile, regarding temperament and character in patients with central serous retinopathy, as compared to healthy subjects.